INVITRO OPTIMIZATION AND COMPARATIVE ANALYSIS OF BACTERIAL AND FUNGAL AMYLASE - PRASAD M.P; SUSHANT SEKHAR (International Journal of Pharma and Bio Sciences, 2013)
The present study was conducted for the isolation of a suitable Amylase producing Bacterial and Fungal strain and optimization of the cultural conditions for the production of amylase enzyme. Studies on the optimum conditions for the production of amylase were performed with isolated and identified bacterial (Bacillus) and fungal (Aspergillus) species. The optimum temperature for amylase production by bacterial species was detected as 350C and by fungal species was detected as 250C. Amylase production was observed at pH 5-9 with maximum at pH 7 for bacteria and pH 6 for fungus. The levels of amylase production varied greatly with the addition of carbon source. Effect of different nitrogen sources revealed that protease peptone and urea were the better nitrogen sources and showed increased enzyme yield. The amylase enzyme was purified by Ammonium sulphate precipitation followed by Dialysis and then column chromatography. The purified Amylase was then analyzed by SDS-PAGE.